The Impact of E-Modules on Students’ Critical Thinking Skills - Sidauruk, Tumiar; Delita, Fitra; Berutu, Nurmala; Yuniastuti, Eni; Elfayetti, Elfayetti (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
E-modules is one of electronic learning materials more useful and efficient in 21st learning. The objectives of this study are to develop an e-module, measure its feasibility and analyze its impact on students’ critical thinking in the Learning Media Course. ADDIE model (Analysis, Design, Development, Implementation and Evaluation) was used in this study. A quasi-experimental research design was carried out to analyze the impact of using e-modules on critical thinking. A total of 40 students in the fourth semester of the Geography Education Department, Social Sciences Faculty, Universitas Negeri Medan were participated in this research. Data collection was used questionnaires and an essay test. Descriptive statistics and inferential statistics were performed for data analysis. The statistical test carried out was a t-test. The research findings showed that the e-module was feasible to apply in lectures and significantly improved students’ critical thinking.